2021
DOI: 10.2478/jeb-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth in the Western Balkans: A Panel Analysis

Abstract: This paper investigates how typical macroeconomic indicators affect the economic growth of Western Balkans countries. A static panel empirical investigation for the period 2010 to 2019 has been conducted using GDP growth rate as the dependent variable, while independent variables in focus include foreign direct investments, remittances, unemployment rate, population growth rate, and control of corruption. The most interesting finding is that a rising share of remittances positively affects economic growth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[80] Found that utilized data over 200 years for both developing and developed countries and found that the effect of the population is dependent on the level of economic growth of countries and concluded that low population in high-income countries is a problem while high population in a low-income country is also another challenge. A similar study by [81][82][83] study was carried out in SSA countries to find that population growth retards economic growth especially where hunger and inequality is the major challenge.…”
Section: Empirical Literature Reviews On Institutional Quality and Ec...mentioning
confidence: 90%
“…[80] Found that utilized data over 200 years for both developing and developed countries and found that the effect of the population is dependent on the level of economic growth of countries and concluded that low population in high-income countries is a problem while high population in a low-income country is also another challenge. A similar study by [81][82][83] study was carried out in SSA countries to find that population growth retards economic growth especially where hunger and inequality is the major challenge.…”
Section: Empirical Literature Reviews On Institutional Quality and Ec...mentioning
confidence: 90%
“…This is consistent with the reason that the weakening of remittances is caused by several things, such as the high level of corruption in the Islamic countries of the world, which undermines the impact of remittances on the economy. (Ziberi & Alili, 2021) Weak institutions, such as a lack of rule of law or regulation. (Kratou & Gazdar, 2015) If remittances are not protected by strong institutions, they cannot be used effectively to create new businesses, invest in infrastructure, or create jobs.…”
Section: Variablesmentioning
confidence: 99%
“…However, the results of the GLS model data also show that there is a difference among the countries of the region in terms of FDI's impact on economic growth. From a review of the literature, it is clear that there is a substantial body of research related to FDI inflow in the countries of the Western Balkans [2,8,11,12,[16][17][18][19][20][21][22][23]. Nevertheless, there is a lack of studies examining the effect of the FDI inflow on the insurance sector in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the reviewed econometric books in relation to the applicable econometric models for testing our hypotheses, as well as based on works that have applied models with panel data specifically to analyze the effect of FDI in the six countries of the Western Balkans [18][19][20] or other authors [32][33][34], we will apply Pooled OLS, Fixed Effects, and Random Effects. Then, using functional tests, we will choose which of these three models is most suitable to use for testing our hypotheses.…”
Section: The Modelmentioning
confidence: 99%